DEGRADASI LIMBAH TAHU DENGAN KOAGULASI FLOKULASI ALUMUNIUM SULFAT DAN FOTOKATALIS TIO2 DALAM TANGKI BERPENGADUK - Tuhu Agung Rachmanto; Egi Pebritama (EnviroUS, 2021)
The tofu Industries was established for food industries who has a positive and negative impacts for environment. Negative effect from tofu industries was a waste that caused impact for environment. Environment pollutions appears from a solid waste (tofu residue) and waste water. Most of all waste water who caused from tofu industries is a thick liquid separated from tofu blocks called “whey”. Waste from tofu industries had a high organic content such as COD and TSS. In this research, several method were used for reduce the organic content. Coagulation with Aluminium sulfate (Al2(SO4)3, could reduce a Chemical Oxygen Demand (COD) content until 50,3% and Total Suspended Solid (TSS) until 81% with doze of coagulant 1000 mg/l. Fotocatalyst TiO2 could reduce Chemical Oxygen Demand (COD) 50% with an exposure time 150 minutes.